Tensile data - Rodrigues Pardal; Ganguly, Supriyo; Williams, Stewart; Vaja, Jay (Cranfield University, 2016)
Tensile data from the CMT paper.
Keywords: 'Welding'; 'Manufacturing Processes and Technologies (excl. Textiles)'; 'Mechanical Engineering'